2013
DOI: 10.1158/1078-0432.ccr-12-3280
|View full text |Cite
|
Sign up to set email alerts
|

Unique DNA Methylation Loci Distinguish Anatomic Site and HPV Status in Head and Neck Squamous Cell Carcinoma

Abstract: Purpose: We have utilized a genome-wide approach to identify novel differentially methylated CpG dinucleotides that are seen in different anatomic sites of head and neck squamous cell carcinoma (HNSCC), as well as those that might be related to HPV status in the oropharynx. Experimental Design: We performed genome-wide DNA methylation profiling of primary tumor samples and corresponding adjacent mucosa from 118 HNSCC patients undergoing treatment at Montefiore Medical Center, Bronx, NY using the Illumina Hum… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
105
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(120 citation statements)
references
References 49 publications
12
105
1
2
Order By: Relevance
“…Previous work has shown that HPV-positive tumors have a distinct methylation profile compared with HPV-negative tumors (43,44). To study the influence of HPV integration events on the host cell, we compared the patterns of DNA methylation and gene expression of HNSCCs with and without integration.…”
Section: Hpv Integration Is Associated With a Specific Methylation Simentioning
confidence: 99%
“…Previous work has shown that HPV-positive tumors have a distinct methylation profile compared with HPV-negative tumors (43,44). To study the influence of HPV integration events on the host cell, we compared the patterns of DNA methylation and gene expression of HNSCCs with and without integration.…”
Section: Hpv Integration Is Associated With a Specific Methylation Simentioning
confidence: 99%
“…In addition, The Cancer Genome Atlas (TCGA) head and neck study found that TNF receptor-associated factor 3 (TRAF3) and CYLD genes are commonly mutated and deleted in HPV þ HNSCC (6,8,14). Finally, HPV À HNSCC have relatively low levels of DNA methylation, which is correlated with genomic instability (15), whereas HPV þ HNSCC harbor distinctly hypermethylated genomes (7,8,16,17). Demographic, clinical, molecular, and epigenetic differences between HPV þ and HPV À HNSCC suggest two distinct cancers, yet HPV À status is currently only used for prognosis and not to guide treatment (18).…”
mentioning
confidence: 99%
“…9 Proteomics This article has touched on methodologies and bioinformatics in genomics and epigenetics. Proteomics, the comprehensive evaluation of protein expression, structure, modification and function in biological systems, deserves brief mention here.…”
Section: Single Nucleotide Polymorphism Arraysmentioning
confidence: 99%
“…18 In a study from our own institution, DNA methylation arrays were performed on 118 head and neck SCC tumour-normal pairs. 9 Differentially methylated genes could distinguish between head and neck SCC and normal tissue. Methylation events specific to tumour subsite and to HPV status were also identified.…”
Section: Single Nucleotide Polymorphism Arraysmentioning
confidence: 99%
See 1 more Smart Citation